Nuclear accumulation of protein p53 and histological changes in the rat model of unilateral cryptorchidism - (:unkn) unknown (My University, 2002)
Introduction: Cryptorchidism is accepted as a substantial risk factor for the subsequent development of testis cancer. Since p53 is highly expressed in testicular tumors, this study was undertaken to investigate the abnormal expression of p53 protein and histological changes in a rat model of unilateral cryptorchidism. Material and Methods: Prepubertal rats were rendered mechanically rendered unilaterally cryptorchid on 15th day after the birth. Subsequently, testes were harvested from experimental and sham operated rats at two, four and six months for immunohistochemical and histological studies. Contralateral testes in the experimental groups served as the controls. Results: There were no histological abnormalities observed in the testes of both sham operated and control groups. However, experimentally cryptorchid testes were smaller and accompanied by a prominent change in color. A significant decrease in testicular volume in the cryptorchid group was noted (p < 0.05). Seminiferous tubular atrophy, basement membrane thickening, germ cell loss and spermatogenic arrest were progressively more evident with time, being highest at the sixth month. Immunohistochemical staining on paraffin sections demonstrated positive nuclear reaction for p53 in 14 (93.3%) out of 15 cryptorchid testes. In contrast, sham operated and control groups were completely devoid of any nuclear accumulation of p53. Conclusion: In conclusion, this study confirms that intraabdominal cryptorchid testes are significantly impaired due to abnormal localization. Immunohistochemical positivity for the p53 protein in cryptorchid testes suggests a molecular alteration and may indicate an association between cryptorchidism and testicular carcinogenesis.
Keywords: Cryptorchidism; Protein p53; Rat; Testicular neoplasms; Testis